Poisson's Approach to Useful Life Analysis of Transmission Lines - Sutisna, Sutisna; Priatna, Edvin; Widiyasono, Nur (Teknik Elektro Universitas Siliwangi, 2025)
ABSTRACT: Reliability is defined as the probability of a device or system performing its functions adequately over a period of time under certain operating conditions. Component failure can impact the power supply to customers, and result in high costs associated with loss of power supply and or replacement of components. This article implements the Poisson model in estimating the reliability value of the electric power grid to obtain the useful life of each load bus. This useful life period as an indicator of the period of preventive maintenance. With the estimation of the reliability value using the Poisson Method is shown by obtaining maximum probability which is the best end of system performance. This method was tested on the IEEE 14 bus diagram system. As a sample of the maximum probability test results in bus_2, bus_3, and bus_5 occurred in 14th year, 9th year, and 11th year KEYWORDS:. Reliability Value, Poisson Method, Useful Life